Measured Performance Comparisons between Spatial Multiplexing and Beamforming Arrays in the 28 GHz Band - Dazhi Piao; Xingning Jia; Xiaochuan Ma; Qingxin Guo; Zengrui Li (International Journal of Antennas and Propagation)
A spatial multiplexing (SM) array and a beamforming (BF) array with similar antenna size working at 28 GHz are designed and fabricated. In the SM array, a 4 × 4 MIMO system is realized with each port composed of a four-element subarray. In the BF array, the whole 16 elements are used to formulate a high-gain array. The measured S-parameters are in agreement with the simulated results. For both arrays, the channel capacities are computed by the measured channel matrix and signal-to-noise ratio (SNR) in an office room. Results show that capacity of the SM system is larger than that of the BF system, although the gain of BF array is about 5 dB larger than that of the SM array. However, the capacity of the SM array depends heavily on SNR; specifically, for the 1 dBm transmit power, communication distance R=25 cm, the ergodic capacity of the SM system is 2.76 times that of the BF system, and if R=250 cm, the capacity gain is reduced to 1.45. Furthermore, compared with the BF array, the SM array has a more robust performance over antenna misalignment, because of the wider beamwidth.